2007
DOI: 10.2108/zsj.24.257
|View full text |Cite
|
Sign up to set email alerts
|

Autopodial Development in the Sea Turtles Chelonia mydas and Caretta caretta

Abstract: The manus and pes were studied using whole-mount and histological preparations of ontogenetic series of Chelonia mydas and Caretta caretta. Patterns of connectivity and sequences of chondrification events are similar to those reported for other turtle species, with respect to both the primary axis and the digital arch. There is no evidence of anterior condensations in the region distal to the radius and the tibia, supporting the hypothesis that the radiale and tibiale are absent in turtles. The three middle me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 18 publications
7
44
3
1
Order By: Relevance
“…In a series of articles, Rieppel (e.g., 1992;1993a,b) documented and indicated that chondrification and ossification are decoupled phenomena, confirming this previous observation by de Beer (1937) and by later workers including ourselves (Sheil, 2005;Sá nchez-Villagra et al, 2007). Data presented here for P. sinensis confirms this pattern.…”
Section: The Limb Chondrification Patternsupporting
confidence: 87%
See 1 more Smart Citation
“…In a series of articles, Rieppel (e.g., 1992;1993a,b) documented and indicated that chondrification and ossification are decoupled phenomena, confirming this previous observation by de Beer (1937) and by later workers including ourselves (Sheil, 2005;Sá nchez-Villagra et al, 2007). Data presented here for P. sinensis confirms this pattern.…”
Section: The Limb Chondrification Patternsupporting
confidence: 87%
“…We find no evidence of anterior condensations distal to the radius and the tibia, respectively, suggesting that the radiale and tibiale are absent, as in other turtles examined to date (Burke and Alberch, 1985;Sá nchez-Villagra et al, 2007;Sheil and Portik, 2008;Fabrezi et al, 2009).…”
Section: The Limb Chondrification Patterncontrasting
confidence: 43%
“…The plesiomorphic phalangeal formula for crown turtles is probably 2-3-3-3-3 for both manus and pes (Sánchez-Villagra et al 2007;Delfino et al 2010). Although the phalangeal formula can be used to diagnose taxa, studies on recent species have shown that significant amounts of variation exist (e.g., Minx 1992;Delfino et al 2010).…”
Section: Parachelys Eichstaettensismentioning
confidence: 99%
“…Access to turtles was provided by a commercial vendor (Turtles and Tortoises, Brooksville, FL, USA (Sheil, 2003), T. scripta (Hall, 2000;Sheil and Portik, 2008), C. insculpta (Walther, 1921) and C. caretta (Wyneken, 2001;Sanchez-Villagra et al, 2007)]. …”
Section: Experimental Animalsmentioning
confidence: 99%